Typology of urban agriculture architecture - Aleksandra Nowysz; Elżbieta Trocka-Leszczyńska (Acta Scientiarum Polonorum. Architectura)
The subject of the paper is contemporary urban farming architecture, defined as urban spaces and objects which are located within cities and dedicated to growing of edible plants. This study aims to investigate design that facilitate urban development integrating the life of the city with the food production. To examine it the following methods were used: literature review, case studies, projects descriptions and analysis based on comparison. The urban agriculture architecture typology and selected examples of each type are presented herein.